2014
DOI: 10.1186/1471-2180-14-172
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of curcumin in combination with epigallocatechin gallate (EGCG) versus multidrug-resistant Acinetobacter baumannii

Abstract: BackgroundAcinetobacter baumannii is an opportunistic human pathogen often associated with life-threatening infections in the immunocompromised and the critically ill. Strains are often multidrug-resistant (MDR) and due to the lack of new synthetic antimicrobials in development for treatment, attention is increasingly focused on natural compounds either as stand-alone or adjunctive agents. Curcumin (CCM) is a natural polyphenol found in turmeric and isolated from the plant, Curcuma longa. Curcumin has been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 32 publications
(40 reference statements)
4
50
0
2
Order By: Relevance
“…The combination was clearly bactericidal, and significant synergy was produced, indicated by a >3 log CFU/mL difference between the agents used in combination versus alone. 18 The data presented here with the exception of P. aeruginosa agree with previous results, whereby 2 alone showed no antibacterial activity over 24 h, in time−kill assays. 18 This could be due to the insolubility of 2 or the inability of the compound to pass through the outer cell membrane/cell wall to reach its target.…”
supporting
confidence: 94%
“…The combination was clearly bactericidal, and significant synergy was produced, indicated by a >3 log CFU/mL difference between the agents used in combination versus alone. 18 The data presented here with the exception of P. aeruginosa agree with previous results, whereby 2 alone showed no antibacterial activity over 24 h, in time−kill assays. 18 This could be due to the insolubility of 2 or the inability of the compound to pass through the outer cell membrane/cell wall to reach its target.…”
supporting
confidence: 94%
“…These compounds provide health benefits and show remarkable antimicrobial activity against resistant pathogens [13, 14]. Tea extracts having high concentrations of epigallocatechin gallate (EGCG) and epigallocatechin (EGC) are more potent in antibacterial activity against bacterial pathogens [15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to high content of phenolic compounds, especially flavan-3-ols and phenolic acids, this plant has become very interesting as a source of antimicrobial substances. So far, it was shown that /-/-epigallocatechin gallate, present in great burnet extracts, in combination with curcumin (isolated from Curcuma longa rhizomes) is very effective against multidrug-resistant Acinetobacter baumannii [13]. It was confirmed that extracts form this plant have strong effect against avian E. coli [14].…”
Section: Ta B L Ementioning
confidence: 89%